Pengaruh Hipnosis Terhadap Kecemasan Pada Calon Akseptor KB IUD - Syuhrotut Taufiqoh (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Anxiety about the installation procedure is an obstacle experienced by prospective acceptors of the IUD method. One way to reduce anxiety is to use hypnotherapy techniques. This study aims to determine the effect of hypnotherapy on the anxiety of prospective IUD family planning acceptors.Methods: This research was a quasi-experimental study with a one-group pre-test and post-test approach without a control group. This research was carried out at TPMB Farida Hajri in January - March 2021. The population under study consisted of up to 40 candidate IUD acceptors. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). Test data were analyzed using Wilcoxon.Results: There was a decrease in the anxiety level of prospective IUD acceptors before and after receiving non-pharmacological hypnotherapy by 10.8 points. Based on the calculation results of the Wilcoxon signed rank test, a Z value of -6.145 was obtained with a significance value of < 0.000 (p < 0.05), which was a significant difference before and after the intervention.Conclusion: There are differences in the level of anxiety before and after receiving non-pharmacological therapy in the form of hypnotherapy intervention. Anxiety in family planning acceptors is something that needs to be considered because it can cause an increase in pain scores in IUD acceptors. Based on the results of this study, it is necessary to manage anxiety to increase comfort in inserting the IUD so that it was expected to increase the coverage of contraceptive use, especially IUD contraception.